Deliverable D4.1: VLC modulation schemes - Kumar, Navin (2014)
This report presents the analysis of different modulation schemes D4.1 for VLC systems of the VIDAS project. Considering the final prototype design and application, the deliverable D4.1 was projected. The detail analysis of various modulation schemes are carried out and a robust technique based on direct sequence spread spectrum (DSSS) is followed. DSSS technique though necessitates use of high bandwidth while minimizing the effect of noise. Since the final application does not require very high dat a rate of transmission but robustness against the noise (external lights) becomes necessary. The analysis is followed by model development using Matlab/Simulink. The performance of both of these systems are compared and evaluated. Some of the simulation results are presented.